A Mathematical Compartmental Model for Deradicalization in Indonesia: The SERTV Framework - Asyhar, Ahmad Hanif; Fatmawati, Fatmawati; Windarto, Windarto; Herdicho, Faishal Farel; Abidemi, Afeez (Journal of Multidisciplinary Applied Natural Science, 2026)
Radicalism remains a critical threat to Indonesia's national security and social cohesion, necessitating urgent efforts to understand and mitigate its spread. This study develops a mathematical model to describe the dynamics of radicalization and deradicalization in Indonesia, using a compartmental structure that divides the population into susceptible, extremist, recruiter, treated, and vaccinated groups. The model incorporates a saturated incidence rate to capture the nonlinear effects of radical interactions. Numerical simulations are carried out using the fifth-order Runge–Kutta method to illustrate the transitions between population groups. The results indicate a significant decline in extremist and recruiter populations, while vaccination against radical ideas contributes to long-term resilience. Sensitivity analysis shows that the radicalization rate and recruitment effectiveness are the most influential parameters driving the spread of radicalism. These findings provide new insights into the mechanisms of radicalization and serve as a foundation for designing evidence-based preventive strategies.